Pocket guide to bacterial infections - Balamurugan, K. (Krishnaswamy); Udayakumar, Prithika (Pocket guides to biomedical sciences., 2019)
Pocket Guide to Bacterial Infections provides information pertinent to the behaviour of bacterial cells during their interactions with different cell types of multiple host systems. This book will present the role of various bacterial pathogens affecting the host system. The book is to be organized flexibly so that chapters and topics are arranged with continuity from the former chapters. Each chapter has been made as self-contained as possible to promote this flexibility. This book will discuss each of the virulence properties of the bacteria with reference to their interacting hosts in a larger perspective. Kwey selling features: Summarizes the role various bacterial pahtogens affect the host system Reviews recent advances for combating different types of bacterial infections that infect different body parts Designed as an effective teaching and research tool providing up to date information on bacterial infections Defines important terms Written in a readable and direct writing style